Multilayer structure containing silane coupling agent

Silane coupling agents improve adhesion between PVC and metal layers in anti-corrosion panels by forming covalent bonds, addressing the challenge of high-temperature bonding in existing technologies and enhancing peel strength.

JP2024546235AInactive Publication Date: 2024-12-19DOW GLOBAL TECHNOLOGIES LLC
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024530477
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2021-12-10
Publication Date
2024-12-19
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing technologies face challenges in achieving strong adhesion between polyvinyl chloride (PVC) and metal layers in anti-corrosion panels due to the reliance on polar or secondary valence bonds rather than covalent bonds, especially at high temperatures.

Method used

The use of silane coupling agents to increase the polarity and reactivity of the PVC substrate surface, forming chemical bonds with a binder layer or an interlayer, either as a primer or additive in the tie layer, to promote covalent bonding with the metal layer.

Benefits of technology

The silane coupling agents enhance bonding performance between PVC and metal layers at high temperatures, resulting in improved adhesion and cohesion, as demonstrated by increased 180-degree peel strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024546235000001
    Figure 2024546235000001
  • Figure 2024546235000002
    Figure 2024546235000002
  • Figure 2024546235000003
    Figure 2024546235000003
Patent Text Reader

Abstract

The present disclosure provides embodiments of a multi-layer structure and a method for making the same, comprising at least one polyvinyl chloride (PVC) layer, at least one metal layer, and at least one tie layer adhering a steel layer to the PVC layer, the tie layer comprising 0-95 wt % of at least one ethylene acrylate copolymer and 5-100 wt % of a terpolymer, the multi-layer structure comprising a silane coupling agent disposed in the tie layer, a silane coupling agent added as a primer, or both.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] FIELD OF THE DISCLOSURE

[0002] Embodiments described herein relate generally to multi-layer structures, and specifically to multi-layer structures that include a silane coupling agent. [Background technology]

[0002] Polyvinyl chloride (PVC) is the third most widely produced synthetic plastic polymer in the world (after polyethylene and polypropylene). Due to its excellent properties such as flame retardancy, mechanical strength, corrosion resistance, heat resistance, and foaming properties, PVC is widely used in building materials, flooring, artificial leather, pipes, wire and cable, non-food packaging, bottles, foam materials, sealants, fibers, etc.

[0003] Anticorrosive panels are applied as roofing and walls in various industrial facilities where corrosion protection is highly required. PVC can be utilized in the construction of anticorrosive panels by laminating PVC onto metal using a binder. However, with solvent-free binders, adhesion onto PVC is by polar or secondary valence bonds rather than covalent bonds, so bonding at high temperatures (>80°C) remains a challenge. Therefore, improved PVC to metal bonding is needed in anticorrosive panels. Summary of the Invention

[0004] Embodiments of the present disclosure meet these needs by increasing the polarity and reactivity of the PVC substrate surface and forming chemical bonds with the binder layer or by using a silane coupling agent that provides adhesion during the formation of an interlayer between the substrate and the binder.

[0005] The embodiment incorporating a silane coupling agent can be used either in the form of a primer to pretreat the PVC or as an additive formulated / impregnated into the tie layer resin. The silane coupling agent in the tie layer or added as a primer on the tie layer causes a chemical reaction to form a covalent bond between the PVC and the tie layer. This tie layer that bonds to the PVC can also bond to a metal layer (e.g., steel). Alternatively, another layer (e.g., another tie layer containing maleic anhydride grafted polyethylene resin) may be used to help bond to the metal layer. This tie layer package has good bonding performance at high temperatures.

[0006] According to at least one embodiment of the present disclosure, a multi-layer structure is provided. The multi-layer structure includes at least one polyvinyl chloride (PVC) layer, at least one metal layer, and at least one tie layer that adheres the steel layer to the PVC layer. The tie layer includes 0-95 wt. % of at least one ethylene acrylate copolymer, where the acrylate is selected from vinyl acetate, alkyl acrylate, or maleic anhydride monoester, and 5-100 wt. % of a terpolymer represented by the formula E / V / W, where E is ethylene, V is an acrylic ester comonomer selected from vinyl acetate, alkyl acrylate, or maleic anhydride monoester, and W is a functional group selected from epoxy, maleic anhydride, and carboxyl groups. The multi-layer structure includes a silane coupling agent disposed in the tie layer, a silane coupling agent applied as a primer layer on the PVC layer, or both, where the silane coupling agent is a silane coupling agent having a Z-(CH2) n -SiX q Y 3-q wherein n=1 to 16; X=CH3O or C2H5O-; q=1, 2, or 3; Y=H, C1-C 20 Multilayer structures where Z=H2N-, CH2=CH-, CH2=C(CH3)-COO-, epoxy-CH2O, NH-, OH-, or HS-.

[0007] These and other embodiments are described in more detail in the Detailed Description below. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Certain embodiments of the present application will now be described. These embodiments are provided so that this disclosure will be thorough and complete, and will fully convey the scope of the subject matter to those skilled in the art.

[0009] The term "polymer" refers to a polymeric compound prepared by polymerizing monomers, whether of the same or different types. Thus, the generic term polymer generally includes the term "homopolymer", which refers to a polymer prepared from only one type of monomer, as well as the term "copolymer", which refers to a polymer prepared from two or more different monomers. As used herein, the term "interpolymer" refers to a polymer prepared by polymerization of at least two different types of monomers. Thus, the generic term interpolymer includes copolymers or polymers prepared from more than two different types of monomers, such as terpolymers.

[0010] "Polyethylene" or "ethylene-based polymer" shall mean a polymer containing more than 50 mole percent units derived from ethylene monomers. This includes ethylene-based homopolymers or copolymers (meaning that the units are derived from two or more comonomers). Common forms of ethylene-based polymers known in the art include, but are not limited to, low density polyethylene (LDPE), linear low density polyethylene (LLDPE), ultra low density polyethylene (ULDPE), very low density polyethylene (VLDPE), single-site catalyzed linear low density polyethylene (m-LLDPE), including both linear and substantially linear low density resins, medium density polyethylene (MDPE), and high density polyethylene (HDPE).

[0011] As used herein, the term "propylene-based polymer" or "polypropylene" refers to a polymer that, in polymerized form, contains more than 50 mole percent units derived from propylene monomers. This includes propylene homopolymer, random copolymer polypropylene, impact copolymer polypropylene, propylene / α-olefin copolymer, and propylene / α-olefin copolymer.

[0012] The term "LLDPE" includes resins made using Ziegler-Natta catalyst systems, as well as resins made using single-site catalysts, including but not limited to bismetallocene catalysts (sometimes referred to as "m-LLDPE"), phosphinimine, and constrained geometry catalysts, and post-metallocene molecular catalysts, including but not limited to bis(biphenylphenoxy) catalysts (also referred to as polyaryloxy ether catalysts).LLDPE includes linear, substantially linear, or heterogeneous ethylene-based copolymers or homopolymers. LLDPE contains less long chain branching than LDPE and includes substantially linear ethylene polymers as further defined in U.S. Patent Nos. 5,272,236, 5,278,272, 5,582,923, and 5,733,155, homogeneously branched linear ethylene polymer compositions such as those in U.S. Patent No. 3,645,992, heterogeneously branched ethylene polymers such as those prepared according to the process disclosed in U.S. Patent No. 4,076,698, and blends thereof (such as those disclosed in U.S. Patent No. 3,914,342 or U.S. Patent No. 5,854,045). LLDPE resins may be made by gas phase, solution phase, or slurry polymerization, or any combination thereof, using any type of reactor or reactor configuration known in the art.

[0013] Reference is now made in detail to embodiments of the multilayer structure as described herein. The embodiments of the multilayer structure may include at least one polyvinyl chloride (PVC) layer, at least one metal layer, and at least one tie layer that adheres the metal layer to the PVC layer. The tie layer includes 0-95% by weight of at least one ethylene acrylate copolymer, where the acrylate is selected from vinyl acetate, alkyl acrylate, or maleic anhydride monoester. The tie layer further includes 5-100% by weight of a terpolymer represented by the formula E / V / W, where E is ethylene, V is an acrylic ester comonomer selected from vinyl acetate, alkyl acrylate, or maleic anhydride monoester, and W is a functional group selected from epoxy, maleic anhydride, and carboxyl groups.

[0014] The multi-layer structure further includes a silane coupling agent disposed in the tie layer, a silane coupling agent applied as a primer layer on the PVC layer, or both, the silane coupling agent being Z-(CH2) n -SiX q Y 3-q wherein n=1 to 16, X=CH3O or C2H5O-; q=1, 2, or 3; Y=H, C1-C 20 Alkyl, aryl, CH3OH- or C2H5O-; Z=H2N-, CH2=CH-, CH2=C(CH3)-COO-, epoxy-CH2O, NH-, OH-, or HS-.

[0015] The metal layer may include a variety of materials familiar to those skilled in the art. For example, the metal layer may include steel or aluminum. In certain embodiments, the metal layer may include steel.

[0016] As noted above with respect to the tie layer, the ethylene acrylate copolymer may include an alkyl acrylate, in one or more embodiments, the alkyl acrylate includes methyl acrylate, methacrylate, ethyl acrylate, or n-butyl acrylate, or isobutyl acrylate.

[0017] The ethylene acrylate may contain 0.1 to less than 50 weight percent acrylate monomers, 1 to 40 weight percent acrylate monomers, 5 to 30 weight percent acrylate monomers, 10 to 30 weight percent acrylate monomers, or 15 to 25 weight percent acrylate monomers.

[0018] The tie layer may comprise 0-95% by weight of at least one ethylene acrylate copolymer, 5-90%, 10-80%, 25-75%, 50-75%, or 25-50% by weight of ethylene acrylate copolymer.

[0019] The ethylene acrylate copolymer may have a density of 0.900 to 0.975 grams per cubic centimeter (g / cc), 0.925 to 0.975 g / cc, or 0.930 to 0.950 g / cc. The ethylene acrylate copolymer may have a melt index (I2) of 0.5 to 40 g / 10 minutes (1 to 10 g / 10 minutes, 1 to 5 g / 10 minutes, or 1.5 to 3.5 g / 10 minutes, as measured according to ASTM D1238 (2.16 kg / 190°C). Additionally, the ethylene acrylate copolymer may have a melt temperature of 80 to 100°C, 85 to 95°C, or 90 to 94°C, as measured according to ASTM D3418.

[0020] Further, as noted above, the tie layer may include 5 to 100 weight percent of a terpolymer represented by the formula E / V / W. The ethylene monomer E may be present in the terpolymer in an amount of at least 50 weight percent to 99 weight percent, 55 weight percent to 90 weight percent, 60 to 85 weight percent, 65 to 80 weight percent, or 70 to 80 weight percent.

[0021] As further noted above, the acrylic ester comonomer V is selected from vinyl acetate, an alkyl acrylate, or a maleic anhydride monoester. In certain embodiments, monomer V can include vinyl acetate. The acrylic ester comonomer V can be present in the terpolymer in an amount of 0.1-50%, 1-45%, 5-30%, 5-25%, 10-25%, or 10-20% by weight of the terpolymer.

[0022] The W functional group comonomer is selected from epoxy, maleic anhydride, and carboxyl. In one or more embodiments, the epoxy monomer comprises glycidyl methacrylate. The W functional group can be present in an amount of 0.1-50%, 1-45% by weight in the terpolymer, 2-30%, 3-20%, or 5-10% by weight in the terpolymer.

[0023] The terpolymer may have a density of 0.925 to 0.975 grams per cubic centimeter (g / cc), 0.930 to 0.970 g / cc, or 0.940 to 0.960 g / cc. The terpolymer may have a melt index (I2) of 0.5 to 20 g / 10 minutes (2 to 15 g / 10 minutes, 4 to 10 g / 10 minutes, or 7 to 9 g / 10 minutes, as measured according to ASTM D1238 (2.16 kg / 190° C.). Additionally, the terpolymer may have a melt temperature of 70 to 100° C., 75 to 90° C., or 80 to 85° C., as measured according to ASTM D3418.

[0024] In one or more embodiments, the tie layer includes both an ethylene acrylate copolymer and a terpolymer. In one embodiment, the tie layer may include 5-95% by weight of the ethylene acrylate copolymer and 5-95% by weight of the terpolymer. In further embodiments, the tie layer may include the ethylene acrylate copolymer in an amount ranging from a lower limit of 5%, 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, or 90% by weight to an upper limit of 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, or 95% by weight. Similarly, the tie layer may include the terpolymer in an amount ranging from a lower limit of 5 wt%, 10 wt%, 20 wt%, 30 wt%, 40 wt%, 50 wt%, 60 wt%, 70 wt%, 80 wt%, or 90 wt%, to an upper limit of 20 wt%, 30 wt%, 40 wt%, 50 wt%, 60 wt%, 70 wt%, 80 wt%, 90 wt%, or 95 wt%.

[0025] Furthermore, the multilayer structure is Z-(CH2) n -SiX q Y 3-q wherein n=1-16; X=CH3O or C2H5O-; q=1, 2, or 3; Y=H, C1-C 20 Alkyl, aryl, CH3OH- or C2H5O-; Z=H2N-, CH2=CH-, CH2=C(CH3)-COO-, epoxy-CH2O, NH-, OH-, or HS-. In a further embodiment, Z=H2N-.

[0026] In certain embodiments, the silane coupling agent may include one or more of the following structures: [ka]

[0027] In addition, the silane coupling agent can include one or more alkoxysilanes, aminosilanes, or aminoalkoxysilanes.In addition, the silane coupling agent can include one or more of the following: (3-aminopropyl)trimethoxysilane (CAS 13822-56-5); (3-aminopropyl)triethoxysilane (CAS 919-30-2); 3-aminopropyl(diethoxy)methylsilane (3179-76-8); N-[3-(trimethoxysilyl)propyl]ethylenediamine (CAS 1760-24-3); (3-((2-aminoethyl)amino)propyl)silanetriol (CAS 68400-09-9); and 3-triethoxysilylpropyl)ethylenediamine (CAS 5089-72-5).

[0028] As mentioned above, the silane coupling agent may be added as a primer layer, may be incorporated into the tie layer, or may be both. When added as a primer layer, the silane coupling agent is present in an amount of 0.01 to 100 g / m 2 , 1~20g / m 2 , or 5 to 10 g / m 2 Alternatively, if incorporated into the tie layer, the tie layer comprises 0.01 to 10 wt %, 0.5 to 7.5 wt %, or 1 to 5 wt % of the silane coupling agent.

[0029] The multi-layer structure of the present invention may have a variety of uses: As mentioned above, the multi-layer structure may be incorporated into a corrosion protection panel.

[0030] Optional ingredients Various optional ingredients are contemplated for the multi-layer structure For example, the multi-layer structure may include an antioxidant (AO). These AOs are IRGANOX 1010(CAS No.6683-19-8), IRGANOX 1024(CAS No.32687-78-8), IRGANOX 1035(CAS No.41484-35-9), IRGANOX 1076(CAS No.2082-79-3), IRGANOX 1098(CAS No.23128-74-7), IRGANOX 1135(CAS No.125643-61-0), IRGANOX 259(CAS No.35074-77-2), IRGANOX 1330(CAS No.1709-70-2), IRGANOX 3114(CAS No.27676-62-6), IRGANOX 565(CAS No. 991-84-4), IRGANOX 245 (CAS No. 36443-68-2), IRGANOX 3052 (CAS No. 61167-58-6), IRGANOX 3790 (CAS No. 40601-76-1), IRGANOX 1520 (CAS No. 110553-27-0), IRGANOX 1726 (CAS No. 110675-26-8); hindered phenol-based AOs such as IRGAFOS 168 (CAS No. 31570-04-4), IRGAFOS 38 (CAS No. 145650-60-8), IRGAFOS 12 (CAS No. 80410-33-9), IRGAFOS TNPP (CAS The AOs may include, but are not limited to, phosphite AOs including IRGANOX PS 800 (CAS No. 26523-78-4); thioether AOs such as IRGANOX PS 800 (CAS No. 123-28-4), IRGANOX PS 802 (CAS No. 693-36-7), or a combination of two or more AOs thereof.

[0031] Additional polymeric materials are contemplated for use in the multi-layer structure. For example, the multi-layer structure may include one or more of polymethyl methacrylate (PMMA), HDPE, LLDPE, polyolefin elastomer (POE), polypropylene, ethylene-propylene copolymer, and combinations thereof.

[0032] Additionally, the tie layer may optionally contain up to 1% by weight of a non-ionic wetting agent which may be added when the silane is dissolved in water prior to application as a primer.

[0033] Manufacturing method Various methodologies are considered suitable for preparing the multilayer structure of the present invention. For example, the silane coupling agent can be incorporated into the polymer resin in the tie layer using various blending and pre-blending techniques. For example, the blending can be performed by immersion process (e.g., by blending the silane with the resin and shaking for several hours at a temperature lower than the melting temperature), blending in a twin screw extruder, blending in a BUSS kneader, blending in a single screw extruder, blending in a batch mixer. Furthermore, when added to a tie layer film, the tie layer film can be produced using blown film technology or cast film technology.

[0034] When the silane coupling agent is applied as a primer layer, the primer layer can be coated by spray coating, roller coating, or immersion of the PVC surface in a silane solution.

[0035] Test Method

[0036] 180 degree peel strength test

[0037] The 180° peel strength test was performed on an Instron testing machine equipped with an environmental cabinet according to ASTM D1876. The test specimens were heated at 50° C. and then pulled at 100 mm / min until breakage.

[0038] density

[0039] Density is measured in grams per cubic centimeter (g / cm) according to ASTM D792-13. 3 ) was reported.

[0040] Melt Index (I2)

[0041] Melt index (I2) was measured according to ASTM D 1238-13 using the following conditions: 190° C. / 2.16 kilograms (kg). Results were reported in grams dissolved per 10 minutes (g / 10 min). EXAMPLES

[0042] The following examples illustrate features of the present disclosure, but are not intended to limit the scope of the disclosure. The following experiments analyzed the performance of embodiments of the multi-layer structures described herein.

[0043] Materials used

[0044] The PVC film was supplied by Sinopharm Chemical Reagent Co., Ltd (SCRC) and had dimensions of 100 μm thickness and 1 m width.

[0045] Bonding Resin 1 is an ethylene methacrylate copolymer containing 24% by weight of a methacrylate comonomer. Bonding Resin 1 has a melt index (I2) of 2 g / 10 min (measured according to ASTM D1238 (2.16 kg / 190° C.)).

[0046] Bonding resin 2 is a terpolymer of ethylene monomer, 15% by weight vinyl acetate (VA) comonomer, and 9% by weight glycidyl methacrylate (GMA) comonomer. Bonding resin 2 has a melt index (I2) of 8 g / 10 min (measured according to ASTM D1238 (2.16 kg / 190° C.)).

[0047] Binder resin 1 and binder resin 2 can be prepared by standard free radical copolymerization techniques using high pressure and operating in a continuous mode. Monomers are fed to the reaction mixture in a ratio related to the reactivity of the monomers and the amount desired to be incorporated. In this way, a uniform and approximately random distribution of monomer units along the chain is achieved. Polymerization in this manner is well known and is described in U.S. Pat. No. 4,351,931 (Armitage), which is incorporated herein by reference. Other polymerization techniques are described in U.S. Pat. No. 5,028,674 (Hatch et al.) and U.S. Pat. No. 5,057,593 (Statz), both of which are incorporated herein by reference.

[0048] The silane coupling agents used in the experiments are listed in Table 1 below.

[0049] [Table 1] *Supplied by Guotai Huarong New Chemical Materials Co., Ltd.

[0050] Specimen Preparation Process

[0051] combination

[0052] With reference to the test specimens in Tables 2 and 3, Bonding Resin 1 and Bonding Resin 2 were fed into a Brabender mixer at 150° C. with the rotor speed set at 40 rpm until the polymers were melted. The resin mixture was spun at 40 rpm for an additional 5 minutes. The compound was then cut into small pieces for later use.

[0053] Preparation of films

[0054] A small piece of the compound was then placed between two Mylar sheets and then sandwiched in a hot press and preheated at 150°C for 10 minutes. The pressed compound was evacuated 8 times and then held at 150°C and 10 MPa (pressure between the top and bottom plates of the hot press) for an additional 5 minutes. The film was then cooled to room temperature within 5 minutes at a pressure of 10 MPa. The film thickness of all film specimens in the table was 100 μm.

[0055] Preparation of the laminate

[0056] The film was sandwiched between two PVC films with dimensions of 10 cm x 10 cm. Before sandwiching, the silane composition or Table 2 and Table 3 were added onto the PVC film as a primer layer. Specifically, the silane composition was diluted with a solvent (ethanol) to produce a 2 wt% silane solution. The silane solution was coated onto the PVC surface, and then dried at 60°C for 3 minutes to remove the solvent. The amount of silane added was calculated according to the following formula 1.

[0057] W=(W2-W1)*100; Formula 1

[0058] where W is the amount of silane added (g / m 2 ) and W1 is 10×10 cm 2 W is the weight of the PVC film; W2 is the total weight of the PVC and dry silane primer.

[0059] The primed PVC specimens were then laminated at a temperature of 180° C. and a pressure of 0.8 MPa for 10 seconds. The laminated sheets listed in Tables 2 and 3 were cut into 10 cm×2.5 cm specimens for further testing. The peel strength results are shown below.

[0060] [Table 2] CE = Comparative Example IE = Inventive Example

[0061] Referring to Table 2, Comparative Example 1 (CE-1) containing Binder Resin 2 without a silane prime showed a 180° peel strength of 0.42±0.03 N / mm at 50° C. In contrast, the inventive example (IE) primed with silane showed a peel strength of 1.78 N / mm or greater. From a qualitative standpoint, most of the IE specimens showed rupture or cohesive failure of the PVC.

[0062] [Table 3]

[0063] Table 3 shows the peel strength of blends of Tie Resin 2 and Tie Resin 1 with and without the silane primer. As shown, all IE specimens had higher peel strengths than the unprimed CE specimens, demonstrating the benefit of the tie layer-silane primer.

[0064] It will be apparent that modifications and variations are possible without departing from the scope of the present disclosure, as defined in the appended claims. More specifically, although certain aspects of the present disclosure are identified herein as preferred or particularly advantageous, it is contemplated that the present disclosure is not necessarily limited to those aspects.

Claims

1. 1. A multi-layer structure comprising at least one polyvinyl chloride (PVC) layer, at least one metal layer, and at least one tie layer adhering the steel layer to the PVC layer, The bonding layer comprises: 0 to 95 weight percent of at least one ethylene acrylate copolymer, the acrylate being selected from vinyl acetate, an alkyl acrylate, or a maleic anhydride monoester; 5-100 wt. % of a terpolymer represented by the formula E / V / W, where E is ethylene, V is an acrylic ester comonomer selected from vinyl acetate, alkyl acrylate, or maleic anhydride monoester, and W is a functional group selected from epoxy, maleic anhydride, and carboxyl groups; The multi-layer structure includes a silane coupling agent disposed in the tie layer, a silane coupling agent applied as a primer layer on the PVC layer, or both, and the silane coupling agent is selected from the group consisting of Z-(CH 2 ) n -SiX q Y 3-q where n=1-16; X=CH 3 O or C 2 H 5 O-; q=1, 2, or 3; Y=H, C 1 -C 20 Alkyl, aryl, CH 3 OH- or C 2 H 5 O-; Z=H 2 N-, CH 2 =CH-, CH 2 = C(CH 3 )-COO-, epoxy-CH 2 A multilayer structure in which the groups are O, NH-, OH-, or HS-.

2. 10. The multi-layer structure of claim 1 , wherein the silane comprises the following structure: 【Chemistry 1】

3. 3. The multi-layer structure of claim 1 or 2, wherein the metal layer comprises steel or aluminum.

4. The multilayer structure according to any one of claims 1 to 3, wherein the silane coupling agent is present in the primer layer.

5. The primer layer has a thickness of 0.01 to 100 g / m 2 5. The multi-layer structure of claim 4, applied in an amount of

6. The multi-layer structure of claim 1 , wherein the silane coupling agent is incorporated into the tie layer.

7. The multi-layer structure of claim 6, wherein the tie layer comprises 0.01 to 10 weight percent of a silane coupling agent.

8. Z=H 2 The multilayer structure of any one of claims 1 to 7, which is N-.

9. The multilayer structure of any one of claims 1 to 8, wherein the alkyl acrylate comprises methyl acrylate, methacrylate, ethyl acrylate, or n-butyl acrylate or isobutyl acrylate.

10. The multilayer structure of any one of claims 1 to 9, wherein the ethylene acrylate copolymer comprises from 0.1 to less than 50 weight percent acrylate.

11. The multilayer structure of any one of claims 1 to 10, wherein the epoxy monomer comprises glycidyl methacrylate.

12. 12. The multilayer structure of claim 1, wherein the terpolymer comprises 0.1 to 50% by weight of acrylic ester comonomer V.

13. 13. The multilayer structure of any one of claims 1 to 12, wherein the terpolymer comprises 0.1 to 50% by weight of functional group W.

14. 14. The multilayer structure of any one of claims 1 to 13, wherein the tie layer comprises 5 to 95 weight percent ethylene acrylate copolymer and 5 to 95 weight percent terpolymer.

15. A corrosion protection panel comprising any of the multi-layer structures according to any one of claims 1 to 14.

Citation Information

Patent Citations

  • PVC (polyvinyl chloride) / metal bonding hot melt adhesive film and preparation method thereof

    CN103756577A

  • Production of heavy metal adsorbent using PVC as raw material

    JP1977088283A

  • Adhesive structure and metal laminate using the same

    JP1996099387A

  • Thermosetting adhesive composition

    JP1997176595A

  • Composite material of metal and resin

    JP2019025859A